ASSESSMENT AND MOTIVATION IN THE PERSONNAL MANAGEMENT SYSTEM IN AGRICULTURAL ENTERPRISES - Poliuk , M. I. (The actual problems of regional economy development, 2018)
In the article it is investigated scientific approaches to the organization of assessment and motivation of personnel in the management system at enterprises. The theoretical approaches to the formation of personnel management in the context of various historical theories of management are analyzed. The effective structure of the personnel management system is substantiated, which consists of: strategic HR-management; creation of organizational culture; personnel accounting; planning; formation; assessments; motivation and staff development. The specific features of the formation of the personnel management system in agricultural enterprises are investigated. On the basis of the conducted sociological research, an assessment was made of the importance and availability of various components of the personnel management system in agricultural enterprises. It has been revealed that the most important components such as strategic HR management, organizational culture, staff assessment and motivation are poorly developed in existing agricultural businesses.